3D model for optimising the communication topologies of iterated N-players prisoners' dilemma. (2018) - Almanasra, Sally; Suwais, Khaled
The evolution of cooperative behaviour in iterated N-players prisoners' dilemma (INPPD) is studied over several communication topologies. Existing models presented several solution models for evolving the cooperative behaviour among INPPD players. The researches revealed that none of the existing models pay attention to the pivot role of the best players in evolving the cooperative behaviour. In this paper, we present a 3D model for optimising communication topologies of INPPD to increase the cooperative rate between players. The 3D model aims to transfer well-known topologies to new 3D topologies that give the best players major roles in the game. This is important as exchanging experiences between players is essential for evolving effective cooperation. Concerning the evolutionary algorithm, this model was designed with the support of a genetic algorithm with synchronous updating to evolve the players' strategies. The results showed that the 3D model could increase the cooperative rate dramatically when compared to the original communication topologies.